The ragamuffin Gospel - Manning, Brennan (Sisters, Or. : Multnomah Publishers, 2000)
"Most of us believe in God's grace .. in theory. But somehow we can't seem to apply it in our daily lives ..."--Back cover.
Foreword / Michael W. Smith -- Foreword / Ben Pearson -- Testimony / Rich Mullins -- 1. Something Is Radically Wrong -- 2. Magnificent Monotony -- 3. Ragamuffin Gospel -- 4. Tilted Halos -- 5. Cormorants and Kittiwakes -- 6. Grazie, Signore -- 7. Paste Jewelry and Sawdust Hot Dogs -- 8. Freedom from Fear -- 9. Second Call -- 10. Victorious Limp -- 11. Touch of Folly -- Guide for Reflection and Prayer -- Scandal of Grace Ten Years Later.
Includes bibliographical references (pages 205-214).
Keywords: God (Christianity) -- Love